Metal-Enhanced Adsorption of High-Density Polyelectrolyte Nucleation-Inducing Seed Layer for Highly Conductive Transparent Ultrathin Metal Films - Wang, Zenggui; Yang, Xi; Yang, Zhenhai; Guo, Wei; Lin, Liujin; Li, Nan; Jiang, Ershuai; Zhang, Jianfeng; Yan, Baojie; Ye, Jichun (Frontiers in Materials, 2019)
In recent years, ultrathin Ag films (UTAFs), which are attractive owing to its extremely low resistance, relatively high transparency, excellent mechanical flexibility and mature mass production, have been reported as potential candidates to replace traditional indium tin oxide (ITO). To achieve a high-quality UTAF, a nucleation-inducing seed layer (NISL) is required to address the issue of irregular Ag islands growth. However, the structures of films so deposited are still far from being ideal and consist of rough surfaces with high densities of voids and grain boundaries when the film thickness is less than ~6 nm. Here, a hybrid structure composed of a gold (Au)/polyethyleneimine (PEI) bilayer is employed as a high-density NISL for the fabrication of an UTAF. Compared to the conventional single-layered PEI NISL that physisorbed on the substrate via the weak electrostatic attraction between the negatively charged substrate and the positively charged amine groups in PEI, our novel bilayered Au/PEI NISL exhibits a much higher density of nucleation sites due to the formation of strong coordinate covalent bonds between the Au atoms and amine groups. As a result, the percolation threshold thickness of the UTAF based on the Au/PEI bilayer can be reduced to as low as 3 nm. After capping with a high-refractive-index tantalum pentoxide (Ta2O5) anti-reflection layer, the resultant Au/PEI/8 nm Ag/30 nm Ta2O5 (APAT) electrode exhibits an excellent optoelectrical performance with a sheet resistance of 9.07 Ω/sq and transmittance of 92.9% in the spectral range of 400-800 nm as well as outstanding long-term environmental and mechanical stabilities. The findings demonstrate a novel strategy for the development of high-performance UTAF-based transparent electrodes.